Еквівалентність у перекладі ділового дискурсу - Баклан, Ірина Миколаївна; Baklan, I. М. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті охарактеризовано загальний стан розвитку дослідження перекладацької еквівалентності, розкрито поняття нормативної еквівалентності в перекладі ділового дискурсу, наведено залежність еквівалентності від жанрової специфіки текстів, зазначено основні перекладацькі стратегії, націлені на досягнення еквівалентності.There is normative equivalence between source text and target text which means usage of definite language norms towards a choice of language tools on syntactical and lexical levels. Extralinguistic and sociolinguistic factors of text formation, perception and interpretation are to be taken into account in business discourse translation. Measures of genre classification are text exhaustiveness, homogeneity and completeness. The business discourse translation strategies include saving of communicative function, text structure and similar reality representation in source and target texts. The equivalence degree can be researched empirically with the help of functional-stylistic text analysis. Material resources could be both translations and parallel texts.
Equivalence in Translation of Business Discourse
Keywords: вихідний текст; source text; діловий дискурс; business discourse; динамічна еквівалентність; dynamic equivalence